Disease-Specific Quality Indicators for Outpatient Antibiotic Prescribing for Respiratory Infections (ESAC Quality Indicators) Applied to Point Prevalence Audit Surveys in General Practices in 13 European Countries - Vellinga, Akke; Luke-Currier, Addiena; Garzón-Orjuela, Nathaly; Aabenhus, Rune; Anastasaki, Marilena; Balan, Anca; Böhmer, Femke; Lang, Valerija Bralić; Chlabicz, Slawomir; Coenen, Samuel; García-Sangenís, Ana; Kowalczyk, Anna; et al. (Antibiotics (Basel), 2023)
Up to 80% of antibiotics are prescribed in the community. An assessment of prescribing by indication will help to identify areas where improvement can be made. A point prevalence audit study (PPAS) of consecutive respiratory tract infection (RTI) consultations in general practices in 13 European countries was conducted in January–February 2020 (PPAS-1) and again in 2022 (PPAS-4). The European Surveillance of Antibiotic Consumption quality indicators (ESAC-QI) were calculated to identify where improvements can be made. A total of 3618 consultations were recorded for PPAS-1 and 2655 in PPAS-4. Bacterial aetiology was suspected in 26% (PPAS-1) and 12% (PPAS-4), and an antibiotic was prescribed in 30% (PPAS-1) and 16% (PPAS-4) of consultations. The percentage of adult patients with bronchitis who receive an antibiotic should, according to the ESAC-QI, not exceed 30%, which was not met by participating practices in any country except Denmark and Spain. For patients (≥1) with acute upper RTI, less than 20% should be prescribed an antibiotic, which was achieved by general practices in most countries, except Ireland (both PPAS), Croatia (PPAS-1), and Greece (PPAS-4) where prescribing for acute or chronic sinusitis (0–20%) was also exceeded. For pneumonia in adults, prescribing is acceptable for 90–100%, and this is lower in most countries. Prescribing for tonsillitis (≥1) exceeded the ESAC-QI (0–20%) in all countries and was 69% (PPAS-1) and 75% (PPAS-4). In conclusion, ESAC-QI applied to PPAS outcomes allows us to evaluate appropriate antibiotic prescribing by indication and benchmark general practices and countries.